Corporate social (ir)responsibility in media and communication industries - Sandoval, Marisol (Javnost (Ljubljana), 2013)
Microsoft is the most socially responsible company in the world, followed by Google on rank 2 and The Walt Disney Company on rank 3 - at least according to the perceptions of 47,000 people from 15 countries that participated in a survey conducted by the consultancy firm Reputation Institute. In this paper I take a critical look at Corporate Social Responsibility in media and communication industries. Within the debate on CSR media are often only discussed in regard to their role of raising awareness and enabling public debate about corporate social responsibility. What is missing are theoretical and empirical studies about the corporate social (ir)responsibility of media and communication companies themselves. This paper contributes to overcoming this blind spot. First I systematically describe four different ways of relating profit goals and social gaols of media and communication companies. I argue for a dialectical perspective that considers how profit interests and social responsibilities mutually shape each other. Such a perspective can draw on a critical political economy of media and communication. Based on this approach I take a closer look at Microsoft, Google and The Walt Disney Company and show that their actual practices do not correspond to their reputation. This analysis points at flaws in the concept CSR. I argue that despite these limitations CSR still contains a rational element that can however only be realised by going beyond CSR. I therefore suggest a new concept that turns CSR off its head and places it upon its feet.
Keywords: communication medium; mediji; komunikacije; podjetja; korporacije; družbena odgovornost; dobiček